Methodological Approach for the Study and Representation of Complex Behaviors on Electricity Markets (2016)
In the this paper, we show a methodological summary to simulate and understand the complex behavior of energy market models. The goal of this work is to propose the business approach of system dynamics, with the dynamical systems and its mathematical point of view. Additionally we present two ways to perform sensitivity analysis on models based on system dynamics. The first one is numerical sensitivity analysis, and the second one is using Poincaré maps. Finally, we conclude that there is complementarity between the mathematical framework and the business applications for the market. This will allow us to achieve greater exploitation for our models.